De traditionele hofhouding bij de Bin Kanyok van Zaire - Wymeersch, Patrick (Afrika Focus, 1989)
This description represents what was more or less an ideal conception of political organization and kingship before the colonial period. If the traditional systems of ruling still remain, the material symbolism of kingship disappeared mostly in the scene of daily life in the king’s large capital. cLooking at the political organization, two seemingly contradictory features emerge. On the one hand, there are the politically quasi-independent lineages living in the villages. The chief or eldest of a lineage is at the same time chief of the whole village. On the other hand, there is the formal political organization, build on a hierarchical model and imposed from the top. This political system is notable for its very high degree of centralization, and especially for the strong authority and power of the divine king. For the purpose of government, the kingdom is divided into sub-districts, containing several villages of an area, districts and provinces. They all depend, in hierarchy,from the capital. The capital accommodates most of the members of the royal family, numerous wives and children from the king and the ministers. The king’s compound, standing in the middle of the capital, is surrounded by afence. This compound is divided into four specific parts and contains several houses and the palace of the king. On both sides of the royal compound, there is a main street where the ministers and theirfamilies live. The king’s person is surrounded by a number of taboos. No one could see him eat in his private kitchen. The principal problem in the political organization is that of the administering the rest of the Kanyok empire, of keeping as a political unit a population divided into autonomous lineages. The model that is followed is, in general, typical of the kingdoms of the southern savanna belt of Zaire. Therefore the structure is pyramidal: the king at the apex delegates his power and authority to the governors. Their position duplicates that of the king, but on a smaller scale. The king is assisted by his ministers to whom he assigned highly specific functions. The king still remains the main focus for all the Bin Kanyok. KEYWORDS : Bin Kanyok, royal court, traditional political systems, Zaire.